Australasian radiographers’ choices of immobilisation strategies for paediatric radiological examinations - Christie, Simon; Ng, Curtise; Sá dos Reis, C. (2020)
Introduction: Immobilisation may be necessary to ensure patient safety and examination success in paediatric medical imaging. Little guidance exists regarding the selection of different immobilisation methods. The purpose of this study was to explore radiographers’ selection of immobilisation methods in paediatric medical imaging and the influences on their choices. Methods: Ethical approval was obtained. A mixed methods approach consisting of online questionnaire distribution followed by individual interviews was used to explore Australasian radiographers' self-reported patterns of immobilisation use and the underlying reasons and beliefs. Quantitative data were described using frequency data, with a Fisher's Exact test used to determine any association between demographic variables and immobilisation methods. Qualitative data were evaluated using content analysis. Results: Sixty-five radiographers returned completed questionnaires, with seven participating in interviews. Psychological immobilisation methods were preferred to minimise patient pain and distress, but physical methods were considered more effective, with parental holding the most likely method to be used (63/65, 96.9%). Participants assumed certain methods to be more appropriate based on patient age and examination type, but adapted their choices based on many other factors, seeking to provide personalised care. Further training was strongly desired (48/64, 75.0%). Participants disagreed on whether introducing written guidance would be beneficial (33/62, 53.2%). Conclusion: Choosing an immobilisation method appears to be a case-by-case activity requiring critical assessment of multiple factors in order to balance patient care with examination success. Implications for practice: Improvements in quality and quantity of education are recommended to enhance radiographers’ ability to make choices based on all relevant factors.